The Religion of a Scientist - Coulter, John M. (The biblical world, 1913)
On another page will be found a contribution by Professor Coulter to a symposium on evolution. In his present paper he speaks as an active church worker as well as one of the leading scientists of America. The attitude which Professor Coulter takes we believe is characteristic of an increasing number of scientists. Having once distinguished the essential elements of religion from the various doctrinal systems with which men have attempted to explain religion, they see that Christianity is something vastly more than speculation and ecclesiastical authority. To use the happy expression which, unless we mistake, Professor Coulter himself originated, they are ready to accept the "old gospel but not a Middle-Age gospel."